2010
DOI: 10.1371/journal.pmed.1000321
|View full text |Cite|
|
Sign up to set email alerts
|

The Effect of Raltegravir Intensification on Low-level Residual Viremia in HIV-Infected Patients on Antiretroviral Therapy: A Randomized Controlled Trial

Abstract: In a double-blind trial, Rajesh Gandhi and colleagues detect no significant reduction in viral load after people with low-level HIV viremia added an integrase inhibitor to their treatment regimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
206
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 272 publications
(228 citation statements)
references
References 21 publications
20
206
2
Order By: Relevance
“…Studies of treatment intensification (44,45), viral evolution during ART (46,47), and in vitro antiviral efficacy (48,49) all support this assumption. Moreover, HIV persistence is widely believed to result solely from the long lifespan or proliferative ability of latently infected cells (3,50).…”
Section: Discussionmentioning
confidence: 96%
“…Studies of treatment intensification (44,45), viral evolution during ART (46,47), and in vitro antiviral efficacy (48,49) all support this assumption. Moreover, HIV persistence is widely believed to result solely from the long lifespan or proliferative ability of latently infected cells (3,50).…”
Section: Discussionmentioning
confidence: 96%
“…Intensifying ART from the normal three-drug regimens to five-drug regimens fails to measurably reduce the size of the latent reservoir (55,56 (73,74). New pharmacologic agents that induce detectable plasma viremia in patients who were previously viremia suppressed on ART could enable bNAbs to find and kill reactivated cells.…”
Section: Targeting the Latent Reservoirmentioning
confidence: 99%
“…However, short-course (28 day) Raltegravir intensification studies on 10 subjects already receiving HAART, with long term suppression, was shown not to reduce their persistent viremia, compared to pre-intensification levels [125]. A recent randomised controlled and double-blinded clinical trial investigating the effect of 12 weeks of Raltegravir intensification on low-level residual viremia in HIV-infected patients did not demonstrate a reduction in plasma HIV-1 levels [126]. On another Raltegravir intensification regime, a transient, but specific increase in episomal cDNA was seen in 30% of the HAART suppressed subjects tested, especially in those that received a protease inhibitor intensification regime.…”
Section: Haart Intensification Studiesmentioning
confidence: 96%